PENINGKATAN KETERAMPILAN KOLABORASI DAN HASIL BELAJAR SISWA MENGGUNAKAN MODEL STUDENT TEAM ACHIEVMENT DIVISION - Waruwu, Ermina; Ginting, Yova Andriani Br (Universitas Negeri Medan, 2024)
This study implemented the Student Team Achievement Division model to enhance collaboration skills and student learning outcomes at SD Santo Petrus Medan. In the classroom action research (PTK), 33 Phase A Class I students in the 2023/2024 academic year participated. The research method encompassed planning, implementation, observation, and reflection, utilizing data collection methods like tests, observation, and documentation. Qualitative descriptive analysis, based on process and product success criteria, was employed. Results indicated a significant rise in applying Student Team Achievement Division and student collaboration skills. Notably, improvements were observed in conveying goals and motivating students (68.75% to 93.75%), presenting information (50% to 87.5%), organizing students into learning groups (29.17% to 87.5%), guiding learning and working groups (46.43% to 92.86%), evaluating learning through quizzes (56.25% to 81.25%), and giving awards (83.33% to 91.67%). Collaboration skills also showed enhancements, including positive interdependence (5.30% to 60.60%), face-to-face interaction (10.10% to 64.64%), individual accountability and responsibility (18.93% to 71.97%), communication (0% to 48.48%), and group work (6.06% to 84.84%). Moreover, student learning outcomes improved notably in proficiency (from 60.61% to 96.97%) and competency (from 5.15% to 3.03%). Recommendations involve boosting teacher creativity, curriculum review, and enhancing learning strategies for comprehensive learning outcomes.